Development and pilot evaluation of a clinic-based mHealth app referral service to support adult cancer survivors increase their participation in physical activity using publicly available mobile apps - Camille E. Short; Amy Finlay; Ilea Sanders; Carol Maher (BMC, 2018)
Abstract Background Participation in regular physical activity holds key benefits for cancer survivors, yet few cancer survivors meet physical activity recommendations. This study aimed to develop and pilot test a mHealth app referral service aimed at assisting cancer survivors to increase their physical activity. In particular, the study sought to examine feasibility and acceptability of the service and determine preliminary efficacy for physical activity behaviour change. Methods A systematic search identified potentially appropriate Apple (iOS) and Android mHealth apps. The apps were audited regarding the type of physical activity encouraged, evidence-based behavioural strategies and other characteristics, to help match apps to users' preferences and characteristics. A structured service was devised to deliver the apps and counselling, comprising two face-to-face appointments with a mid-week phone or email check-up. The mHealth app referral service was piloted using a pre-post design among 12 cancer survivors. Participants' feedback regarding the service's feasibility and acceptability was sought via purpose-designed questionnaire, and analysed using inductive thematic analysis and descriptive statistics. Change in physical activity was assessed using a valid and reliable self-report tool and analysed using paired t-tests. In line with recommendations for pilot studies, confidence intervals and effect sizes were reported to aid interpretation of clinical significance, with an alpha of 0.2 used to denote statistical significance. Results Of 374 mHealth apps identified during the systematic search, 54 progressed to the audit (iOS = 27, Android = 27). The apps consistently scored well for aesthetics, engagement and functionality, and inconsistently for gamification, social and behaviour change features. Ten participants completed the pilot evaluation and provided positive feedback regarding the service's acceptability and feasibility. On average, participants increased their moderate-vigorous physical activity by 236 min per week (d = 0.73; 95% CI = −49 to 522; p = 0.09). Conclusion This study offered initial evidence that a mHealth app referral service for cancer survivors is feasible and acceptable and may increase physical activity levels. The large increase in physical activity is promising, but should be interpreted with caution given the small sample size and lack of control group. Further research is warranted on a larger scale to investigate generalisability, long-term compliance and application in clinical settings.